Potentiation of the Gastroprotective Effect of Ranitidine by Verapamil in Ethanol Induced Ulcer in Rats - Libya, Aisha Dugani (International Journal of Pharmaceutical & Biological Archive, 2014)
Potentiation of the Gastroprotective Effect of Ranitidine by Verapamil in Ethanol Induced Ulcer in Rats